STUDI BENTUK IMPLEMENTASI DAN DAMPAK SOSIAL EKONOMI PENGELOLAAN HUTAN DESA DI NEGERI MORELLA, LEIHITU, MALUKU TENGAH: KASUS DI KUPS TOMASIWA DAN SILIWANGI - Umarella, Nur Rahma Salsabilah; Iskar, Iskar; Imlabla, Wilma (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The purpose of this study was to determine the form of implementation of the Social Forestry program and the Socio-Economic impacts in the management of Village Forests by LPHD in Morella Village. This study used a purposive sampling method, namely LPHD, KUPS. The results of the study showed that there were forms of Implementation of the Social Forestry (PS) program with the Village Forest (HD) management scheme by LPHD in Morella Village, including the formation of KUPS (KUPS Siliwangi, KUPS Toma Siwa, and KUPS Hausihu). The forms of activities include the Agroforestry Program through counseling and planting of seedlings (durian, nutmeg, cloves, and others), planning for clove oil distillation, assistance with sago processing production tools and exploring cooperation assistance with Bank BI for packaging and marketing of sago tumbu. The socio-economic impacts of the existence of Village Forests (HD) include; Social Impacts, namely being able to build community capacity in managing land, respondents' understanding of HD, the existence of social interaction, Cultural values ​​and norms (mutual cooperation, cooperation, sharing experiences, togetherness), Economic Impacts, namely management training and utilizing forest products, increasing the economy independently, increasing community economic efforts, assistance with economic tools/production tools, assistance with business capital, increasing knowledge and skills in product marketing, as well as business/entrepreneurship opportunities, and certainty of forest management.